Feline tibial osteosynthesis: Case report - Miranda, Gabriela; Severino, Hércliton Araújo (Pubvet, 2024)
Diaphyseal fractures of the tibia occur as a result of trauma to the pelvic limb and are a rupture in the continuity of the diaphyseal corticosteroid bone. Animals with this type of fracture must be evaluated to determine whether it is the result of contusion or pathology, such as neoplasms. The study reports the case of a three-year-old mixed-breed feline, weighing three and a half kilos, with non-weight-bearing lameness on the right pelvic limb. The patient was attacked by a dog five days before the appointment. Upon physical examination, it was possible to observe loss of bone continuity in the right pelvic limb in the tibia region. There was an increase in volume, without apparent skin lesions. Radiographic, blood count and biochemical exams were performed. Based on clinical presentation, physical examination, imaging diagnosis and laboratory results, it was concluded that the animal had a fracture of the distal third diaphyseal tibia. Osteosynthesis of the tibia was indicated as treatment, in addition to prescription analgesics to alleviate the patient's pain.
Keywords: feline; osteosynthesis; surgery; tibia